Rescuing Asylum-Seeker Stranded at Sea: Malaysia’s Duty under International Law - Sulaiman, Syafiq; Mat Basir, Salawati; Zamre Mohd Zahir, Mohd (International Journal of Engineering and Technology, 2018)
The protection of the right to life and the duty to rescue persons in distress at sea are the fundamental obligations under two specialized international law regimes which are the international human rights law and the law of the sea. These rules when read together form a strong protection of the human rights of the asylum-seekers stranded at sea. However, often states failed to honour this obligation for various reasons ranging from national security to economic reasons. This article will analyse Malaysiaâ€™s responsibilities as regards the right to life and the duty to rescue of these asylum-seekers. It will also identify the existing international and domestic legal framework relevant to the application of these obligations upon Malaysia and whether it has acted in breach of such obligations. The article then proceeded with suggestions for further improvement that Malaysia can adopt in order to better perform its obligations. This study is a pure doctrinal legal research which is qualitative in nature. The data used in this research is collected from library-based resources. These data were then analyzed by using methods of content analysis as well as critical analysis. The article found that Malaysia has a duty to protect the right to life under international human rights law. Additionally, Malaysia is also bound under the law of the sea to perform its duty to rescue. In view of Malaysiaâ€™s failure to perform these duties in two occasions in the past consequently had resulted in a violation of international law. Therefore, it is suggested that Malaysia should initiate a revision of its national laws and policies regarding treatment of asylum-seekers stranded at sea to be in line with Malaysiaâ€™s duty under international law. Besides, the Malaysian Maritime Enforcement Agency is call upon to comply with the international standards of treatment of persons in distress at sea which includes the asylum-seekers.Â Â